Staff burnout in a psychiatric hospital : a cross-lagged panel design - Corrigan, Patrick W. [Verfasser]; Holmes, E. Paul [Verfasser]; Luchins, Daniel [Verfasser]; Buican, Brett [Verfasser]; Basit, Abdul [Verfasser]; Parks, Joseph J. [Verfasser] (My University, 1994)
"Previous research has shown that burnout in staff members at psychiatric hospitals is significantly associated with state anxiety and collegial support. The directionality of these realtionships may be inferred using a cross-lagged panel design. To do this, 35 staff members representing various clinical disciplines completed measures of burnout, support, and anxiety twice, eight month apart. Burnout comprised three factors: emotional exhaustion, depersonalization, and personal accomplishment. Findings from one cross-lagged panel suggested that emotional exhaustion causes state anxiety. The second panel showed that lack of collegial support caused depersonalization. Understanding causes and effects of burnout for inpatient psychiatric staff may lead to training and resource development that will improve the quality of their work environment." (auhtor's abstract, IAB-Doku) ((en)) Im Rahmen einer empirischen Studie wird dem Burnout von Pflegekräften in der Psychiatrie nachgegangen. Insbesondere wird der Zusammenhang mit Angstzuständen einerseits und der Unterstützung durch Kollegen andererseits untersucht. (IAB)
Burnout des Personals in einem psychiatrischen Krankenhaus
Keywords: G 1.2.2.2 Soziale Sicherungssysteme; Burn-out-Syndrom; Psychiatrie; Pflegeberuf; Berufsproblem; Soziale Unterstützung; Angst; Quantitative Angaben; 1992-1992